Efektivitas Game Edukatif Online Dalam Meningkatkan Kemampuan Grammar Siswa Kelas XI SMA Negeri 1 Gunungsari - Lalu Rangga Dwiputra; Muhammad Adam Maulana (Educational Note, 2026)
This study aims to determine the effectiveness of using online educational games in improving the grammar skills of eleventh-grade students at SMA Negeri 1 Gunungsari. Grammar-related problems often become obstacles in learning English, particularly in aspects of sentence structure and the use of tenses. Innovation in teaching methods through digital media such as educational games is believed to enhance students’ motivation and understanding of grammar materials in a more interactive and enjoyable way. This study employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The sample consisted of two classes: an experimental class that used online educational games and a control class that applied conventional teaching methods. The research instrument was a grammar test administered before and after the treatment. The results of the data analysis showed a significant improvement in the posttest scores of students in the experimental class compared to those in the control class, with a significance value of < 0.05. These findings indicate that the use of online educational games effectively improves students’ grammar skills. Therefore, the implementation of interactive digital learning media can serve as a strategic alternative in the English learning process at the senior high school level. This study also recommends the development and integration of educational games into the curriculum as an innovative effort to enhance students’ language competence.